Efektivitas Komite Audit sebagai Mekanisme Pencegahan Kecurangan - Kusumosari, Larassanti; Nur Rahardjo, Shiddiq (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2023)
This study aims to examine the effect of audit committee effectiveness on financial statement fraud. This research type is explanatory research. The research population is property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during 2020–2022. The sampling method used is a purposive sampling with a total sample of 141 annual reports. The data collection method used content analysis on annual report. This study used logistic regression analysis assisted by EViews13 software. The results showed that the effectiveness of the audit committee, proxied by financial expertise, accounting expertise, and the number of audit committee meetings had negative and significant effect on financial statement fraud. This study contributes by strengthening agency theory, where the findings prove that the effectiveness of the audit committee can overcome agency conflicts and minimize financial statement fraud. Practically, this research contributes to regulators to develop policies regarding the work guidelines of the audit committee as a supervisory body for the financial reporting process and to investors to be able to improve investment decision strategies by analyzing the audit committee structure as a party that ensures the reliability of financial statements which are the basis for corporate decision making.